Dynamically reconfigurable fibre optical spanner - Kolb, Thorsten; Albert, Sahradha; Haug, Michael; Whyte, Graeme (Lab on A Chip, 2014)
In this paper we describe a pneumatically actuated fibre-optic spanner integrated into a microfluidic Lab-on-a-Chip device for the controlled trapping and rotation of living cells. The dynamic nature of the system allows interactive control over the rotation speed with the same optical power. The use of a multi-layer device makes it possible to rotate a cell both in the imaging plane and also in a perpendicular plane allowing tomographic imaging of the trapped living cell. The integrated device allows easy operation and by combining it with high-resolution confocal microscopy we show for the first time that the pattern of rotation can give information regarding the sub-cellular composition of a rotated cell.
EAM Import::2019-03-13

Migration in Confined 3D Environments Is Determined by a Combination of Adhesiveness, Nuclear Volume, Contractility, and Cell Stiffness - Lautscham, Lena; Kaemmerer, Christoph; Lange, Janina; Kolb, Thorsten; Mark, Christoph; Schilling, Achim; Strissel, Pamela; Strick, Reiner; Gluth, Caroline Laura Maria; Rowat, Amy C.; Metzner, Claus; Fabry, Ben (Biophysical Journal, 2015)
In cancer metastasis and other physiological processes, cells migrate through the three-dimensional (3D) extracellular matrix of connective tissue and must overcome the steric hindrance posed by pores that are smaller than the cells. It is currently assumed that low cell stiffness promotes cell migration through confined spaces, but other factors such as adhesion and traction forces may be equally important. To study 3D migration under confinement in a stiff (1.77 MPa) environment, we use soft lithography to fabricate polydimethylsiloxane (PDMS) devices consisting of linear channel segments with 20 ?m length, 3.7 ?m height, and a decreasing width from 11.2 to 1.7 ?m. To study 3D migration in a soft (550 Pa) environment, we use self-assembled collagen networks with an average pore size of 3 ?m. We then measure the ability of four different cancer cell lines to migrate through these 3D matrices, and correlate the results with cell physical properties including contractility, adhesiveness, cell stiffness, and nuclear volume. Furthermore, we alter cell adhesion by coating the channel walls with different amounts of adhesion proteins, and we increase cell stiffness by overexpression of the nuclear envelope protein lamin A. Although all cell lines are able to migrate through the smallest 1.7 ?m channels, we find significant differences in the migration velocity. Cell migration is impeded in cell lines with larger nuclei, lower adhesiveness, and to a lesser degree also in cells with lower contractility and higher stiffness. Our data show that the ability to overcome the steric hindrance of the matrix cannot be attributed to a single cell property but instead arises from a combination of adhesiveness, nuclear volume, contractility, and cell stiffness.
EVALuna2:17547

Optofluidic rotation of living cells for single-cell tomography - Kolb, Thorsten; Albert, Sahradha; Haug, Michael; Whyte, Graeme (Journal of Biophotonics, 2014)
Flow cytometry provides a high throughput, multi-dimensional analysis of cells flowing in suspension. In order to combine this feature with the ability to resolve detailed structures in 3D, we developed an optofluidic device that combines a microfluidic system with a dual beam trap. This allows for the rotation of single cells in a continuous flow, around an axis perpendicular to the imaging plane. The combination of both techniques enables the tomographic reconstruction of the 3D structure of the cell. In addition this method is capable to provide detailed 3D structural data for flow cytometry, as it improves the reconstructed z-resolution of a standard microscopy system to produce images with isotropic resolution in all three axes.
EAM Import::2019-03-08